Giuditta versus Oloferne. Un percorso didattico sull’oratorio musicale - De Luca, Maria Rosa (Musica Docta, 2012)
This paper focuses on La Giuditta, an oratorio in vernacular composed by Alessandro Scarlatti on a libretto by Antonio Ottoboni. Based on a Bible’s deuterocanonical book, the story of the successful deeds of Judith, a beautiful Hebrew who decides to face the terrible Holofernes in order to save Israel, inspired poetic and music-dramatic features of lots of oratorios. Due to her high exemplary virtues, she is frequently represented in figurative arts, as well as in literature, where biblical memory meets poetic invention. So far, this subject gives the opportunity to structure a didactic project, relying music, considered as a point of departure, with historical, artistic and literary disciplines. Two sessions of didactics of listening based respectively on the duet Judith-Nurse, “Deh, rifletti al gran cimento”, and Holofernes’ aria “Togliti da quest’occhi”, in order to introduce the three main characters of Scarlatti’s oratorio and to illustrate two important moments of the plot.